Inhibition of JAK-STAT ERK/MAPK and Glycogen Synthase Kinase-3 Induces a Change in Gene Expression Profile of Bovine Induced Pluripotent Stem Cells. (6th January 2016) - Malaver-Ortega, Luis F.; Sumer, Huseyin; Liu, Jun; Verma, Paul J.
Abstract : Pluripotent stem cells (PSCs) fall in two states, one highly undifferentiated, the naïve state, and the primed state, characterized by the inability to contribute to germinal lineage. Several reports have demonstrated that these states can be modified by changes to the cell culture conditions. With the advent of nuclear reprogramming, bovine induced pluripotent stem cells (biPSCs) have been generated. These cells represent examples of a transient-intermediate state of pluripotency with remarkable characteristics and biotechnological potential. Herein, we generated and characterized biPSC. Next, we evaluated different culture conditions for the ability to affect the expression of the set of core pluripotent transcription factors in biPSC. It was found that the use of 6-bromoindirubin-3-oxime and Sc1 inhibitors alone or in combination with 5-AzaC induced significantly higher levels of expression of endogenous REX1, OCT4, NANOG, and SOX2 . Furthermore, LIF increased the levels of expression of OCT4 and REX1, compared with those cultured with LIF + bFGF. By contrast, bFGF decreased the levels of expression for both REX1 and OCT4 . These results demonstrate that the biPSC gene expression profile is malleable by modification of the cell culture conditions well after nuclear reprogramming, and the culture conditions may determine their differentiation potential.